Grease Lubrication of Self-Mated 60NiTi Bearing Materials - Vellore, Azhar; Walters, Nicholas; Martini, Ashlie (Frontiers in Mechanical Engineering, 2019)
60NiTi is an intermetallic alloy of nickel and titanium that exhibits a unique combination of properties, including hardness comparable to steel, almost twice the elasticity of steel, high corrosion resistance, and tensile strength comparable to ceramics. These properties are very desirable for bearing materials, especially those used in space applications where components must operate efficiently and reliably in harsh conditions. However, despite the fact that most bearings are grease lubricated, there has not been a systematic study of the tribo-performance of greases for 60NiTi lubrication. To address this, we compare the wear and friction of self-mated 60NiTi lubricated by different greases, including those currently used in space missions and general-purpose grease, in boundary lubricated contact. The results provide valuable information to guide selection of grease for 60NiTi contacts as well as lay the groundwork for possible development of new greases specifically for 60NiTi tribo-contacts.